A large‐scale view of Space Technology 5 magnetometer response to solar wind drivers. Issue 4 (17th April 2015) - Knipp, D. J.; Kilcommons, L. M.; Gjerloev, J.; Redmon, R. J.; Slavin, J.; Le, G.
Abstract In this data report we discuss reprocessing of the Space Technology 5 (ST5) magnetometer database for inclusion in NASA's Coordinated Data Analysis Web (CDAWeb) virtual observatory. The mission consisted of three spacecraft flying in elliptical orbits, from 27 March to 27 June 2006. Reprocessing includes (1) transforming the data into the Modified Apex Coordinate System for projection to a common reference altitude of 110 km, (2) correcting gain jumps, and (3) validating the results. We display the averaged magnetic perturbations as a keogram, which allows direct comparison of the full‐mission data with the solar wind values and geomagnetic indices. With the data referenced to a common altitude, we find the following: (1) Magnetic perturbations that track the passage of corotating interaction regions and high‐speed solar wind; (2) unexpectedly strong dayside perturbations during a solstice magnetospheric sawtooth oscillation interval characterized by a radial interplanetary magnetic field (IMF) component that may have enhanced the accompanying modest southward IMF; and (3) intervals of reduced magnetic perturbations or "calms, " associated with periods of slow solar wind, interspersed among variable‐length episodic enhancements. These calms are most evident when the IMF is northward or projects with a northward component onto the geomagnetic dipole. The reprocessed ST5 data are in very good agreement with magnetic perturbations from the Defense Meteorological Satellite Program (DMSP) spacecraft, which we also map to 110 km. We briefly discuss the methods used to remap the ST5 data and the means of validating the results against DMSP. Our methods form the basis for future intermission comparisons of space‐based magnetometer data.